The relationship between social emotional learning competencies according to the (CASEL) model and school violence Afield study on a sample of eight grade students in the city of Lattakia - حسون, نعمه; ريما سعدي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The Research aims to identify the level of social emotional learning competencies according to the CASEL model and the level of school violence among a sample of eighth grade students. It also aims to identify the relationship between school violence and social emotional learning competencies according to the CASEL model. the sample included (216) male and female students. For the research tools, the social emotional competence scale (Zhou & Je, 2012) and the school violence scale (Hassoun, 2021) were applied, after studying their psychometric properties. The results showed that the level of social emotional learning competencies according to the CASEL model among eighth grade students in schools in the city of Lattakia was average, with the arithmetic mean value reaching (3.31), while the level of school violence was low, as the arithmetic mean value reached (1.63).The results also showed that there is an inverse and statistically significant correlation between the level of school violence and the level of social emotional learning competencies according to the CASEL model l among the sample members.